2013
DOI: 10.1080/0144929x.2012.687774
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study on how children interact with pedagogic conversational agents

Abstract: A pedagogic conversational agent (PCA) can be defined as a computer system that interacts with the student in natural language assuming the role of the instructor, a student or a companion. It can have a personality and can generate different sentences according to the agent or the student mood. Empathy with the students' feelings seems to increase their motivation to study. However, the influence of the agent personality and role as well as the students' opinion is still unclear. Therefore, in this article, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…It is expected that it increases the motivation of children and adolescents to learn with their agents [62]. In the future, students could even develop social friendship relationships with their agents [63][64][65][66][67]. Regarding the type of character, 8 out of the 12 reviewed agents have a human shape, usually for older students.…”
Section: Comparisonmentioning
confidence: 99%
“…It is expected that it increases the motivation of children and adolescents to learn with their agents [62]. In the future, students could even develop social friendship relationships with their agents [63][64][65][66][67]. Regarding the type of character, 8 out of the 12 reviewed agents have a human shape, usually for older students.…”
Section: Comparisonmentioning
confidence: 99%
“…A finding by Pérez-Marín [42] also revealed that the 'mood' of the chatbot might also decrease users' desire to leave the chatbot's room. Further research by Jin and Youn found out that the expressive chatbot may get different responses from people with social phobia and those who do not [43].…”
Section: User's Acceptance and Motivationmentioning
confidence: 95%
“…One of the vital features to sustain motivation is providing sufficient empathy for student's emotions. Compassion for the feelings of pupils seems to boost their desire to learn [42].…”
Section: User's Acceptance and Motivationmentioning
confidence: 99%
“…Therefore, there is reason to assume that a conversational application considering the notions of content packaging by means of the relation between thematicity and prosody will benefit from the same advantages as in natural conversation environments. Most of all, conversational avatars in applications for children in educational settings [16], applications for those with special needs [1] as well as for elderly [2] and, in particular, for those with cognitive impairments [17], would greatly benefit from such a communicatively-oriented improvement.…”
Section: Motivation and Backgroundmentioning
confidence: 99%